Contributions to statistical machine learning algorithm - Cui, Yan Hong (Department of Statistical Sciences, 2014)
This thesis's research focus is on computational statistics along with DEAR (abbreviation of differential equation associated regression) model direction, and that in mind, the journal papers are written as contributions to statistical machine learning algorithm literature.